(3GdchcH GdefjQ HTQM GdLGeY GdUZjQs - (3TeS GdOjf eMeO Hf GdYdbei GdTGaYjs; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s ((3eMeO Hf eMeO GdCfHGQi s)
(3BNQgG (B:s
(3aCNHQ Cfg jcQg GdehJ ajRjd Yfg cQGgjI GdehJ GfJgi hbO Je GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B560s
Keywords: (3GdMOjK h GdeUWdMs